A Sober Look at French-English Relations in Quebec - Pugsley, W. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
The Author briefly reviews the historical developments that have led to the present cultural-linguistic situation in Québec business. He then proceeds to a realistic description of Canadian and even international markets for more and more Quebec-based secondary-manufacturing firms, stressing the need for working bilingualism and greater mobility of French-Canadian employees. In such a context, French-Canadians would get greater opportunities, and both sides would gradually abandon prejudice in favour of equity and efficiency.